Upaya meningkatkan keaktifan dan kemampuan berpikir kritis siswa pada materi peluang kejadian majemuk dengan menerapkan model pembelajaran problem based learning - Rosyidah, Novia Mar'atur (Maliki Interdisciplinary Journal, 2024)
This study aims to describe the application of the Problem Based Learning learning model as an effort to increase students' activeness and critical thinking skills. This research is a type of Classroom Action Research (CAR), which consists of two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The research subjects were students of MAN 3 Kediri class 10 J, totaling 39 students. Data collection was carried out by observing one observer. Based on the results of the research above, it can be concluded that students' activeness and critical thinking skills have increased. Active learning in cycle I obtained a score of 49%, followed by cycle II with a score of 62%. Students' thinking skills in cycle I obtained a score of 42% followed by cycle II obtaining a score of 23%.